(untitled) (Research, Society and Development, 2021)
The main objective of this paper is to investigate and report on the occurrence of foreignisms in the poems of AdalcindaCamarão, an Amazonian poet who lived for years in the United States. The research, in a wider sense, also seeks to reveal the possible motives underlying the author’s decision to write either mixing the two languages – Portuguese and English - or entirely in English. Other underlying purposes encompass the exploitation of the author’s life and works aiming at identifying traces thatmight explain the blending of languages in her poems; discussing theories which approach cultural issues and seek to explain which phenomena are related to the events in her life at the in-between place [Braziland the United States]. The corpus of this study is constituted of a selectionof eight poems which deal with the themes of longing and homesickness, melancholy, love, religion, politics, history, and family. To carry out the research, the comparative method was used – a cognitive procedure that favors generalization or differentiation. As a conclusion, we emphasize that the poet gathered memories that, although dormant throughout her life, emerge, interrelate with the American life experience and manifest vividly in poems. The variety of themes approached in her poems and her personal experiencesin Brazil interlaced with those fromthe immersion into the American culture, reveal Adalcinda as a poet with a hybrid identity.